FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) - Natalia, Kristin -; Hasibuan, Lenny Yusmaida; tio, Riris (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Low birth weight (LBW) infants are newborns with a birth weight less than 2500 grams. In 2017, the Simangambat Community Health Center in Bandung City reported the highest number of LBW cases, which amounted to 3,147 cases. The incidence of LBW at the Simangambat Community Health Center fluctuated from 2016 to 2018 and did not reach the set target, which was a maximum of 7%. The causes of LBW can be categorized into three factors: maternal factors, including maternal age, parity, anemia, and pregnancy complications such as antepartum bleeding, preeclampsia, and prenatal care; fetal factors, such as polyhydramnios and multiple gestations; and environmental factors, such as socioeconomic conditions. The objective of this study was to identify factors associated with the occurrence of low birth weight children at Simangambat community health center. The research employed Accidental Sampling, involving a total of 83 respondents. The findings revealed no significant correlation between maternal age and LBW, with a p-value of 0.585. A relationship was found between parity and LBW with a p-value of 0.029. Conversely, there was no link between twin pregnancies and LBW, indicated by a p-value of 0.248. On the other hand, there was a connection between preeclampsia and LBW, with a p-value of 0.038. Additionally, socioeconomic factors, particularly education and family income, were also linked to LBW. The p-value for the education factor was 0.003, and for family income, it was 0.024.